Efficiency and Productivity of Public Hospitals in Pakistan - Ahmad, Umer; Khan, Farhat Ullah; Kanwal, Humaira (Annals of Human and Social Sciences, 2024)
This study aims to measure efficiency and productivity of public hospitals in Pakistan. The efficiency and productivity of public hospitals remains focus of researchers because large amount of public money is spent on them. This research examined 12 DHQ hospitals over the period of 2020–2022 using data envelopment analysis (DEA) and the Malmquist Productivity Index to evaluate efficiency and productivity. Results indicate an average technical efficiency (TE) of 0.926 and scale efficiency (SE) 0.95 with slight improvement during the study period. Overall productivity remained 0.943. Only 5 hospitals showed productivity of 1 while the productivity of the rest of the hospitals remained below 1. Notably, hospitals in Northern Punjab exhibit higher efficiency compared to the Southern and Central Punjab, challenging conventional assumptions linking hospital efficiency solely to economic development levels. The study suggests customized resource allocation and reforms for each hospital’s needs to improve efficieny and productivity.